2016
DOI: 10.1097/acm.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Shortening the Miles to the Milestones: Connecting EPA-Based Evaluations to ACGME Milestone Reports for Internal Medicine Residency Programs

Abstract: The Next Accreditation System requires internal medicine training programs to provide the Accreditation Council for Graduate Medical Education (ACGME) with semiannual information about each resident's progress in 22 subcompetency domains. Evaluation of resident "trustworthiness" in performing entrustable professional activities (EPAs) may offer a more tangible assessment construct than evaluations based on expectations of usual progression toward competence. However, translating results from EPA-based evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Additionally, a study at the University of Mississippi sought to reveal the utility of end-of-shift evaluations of EM residents by clinical faculty. 12 They concluded end-of-shift evaluations “rarely (8%, 372 of 4633) rated a resident as not achieving milestones.” 12 Other studies within anesthesiology, 13 general surgery, 14 and internal medicine 15 residency programs also highlighted the difficulties with evaluating residents and assigning them scores according to the ACGME milestones. Another study by Angus et al 16 surveyed Internal Medicine residents to assess resident perceptions of receiving feedback in the milestone framework.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study at the University of Mississippi sought to reveal the utility of end-of-shift evaluations of EM residents by clinical faculty. 12 They concluded end-of-shift evaluations “rarely (8%, 372 of 4633) rated a resident as not achieving milestones.” 12 Other studies within anesthesiology, 13 general surgery, 14 and internal medicine 15 residency programs also highlighted the difficulties with evaluating residents and assigning them scores according to the ACGME milestones. Another study by Angus et al 16 surveyed Internal Medicine residents to assess resident perceptions of receiving feedback in the milestone framework.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the work in health care entails tasks or responsibilities that must be entrusted to individuals. Research has demonstrated that ability, integrity, and reliability must be fulfilled for someone to trust another person and be willing to be vulnerable to the risks associated with doing so [ 9 ]. An entrusted trainee must demonstrate the necessary competence to execute EPAs unsupervised.…”
Section: W Hat Entrustable Professional Activities Add To Cmentioning
confidence: 99%
“…The difficulty, risk, or complexity of EPAs can be increased based on the ability of trainees. Therefore, medical educators can apply a series of EPAs and supervise the competency level that trainees need to achieve [ 9 ]. EPAs can be executed, and the process and results can be observed separately or simultaneously depending on the competency level of trainees.…”
Section: Introductionmentioning
confidence: 99%
“…Built upon the fundamentals of competency-based medical education, the Accreditation Council for Graduate Medical Education (ACGME) Milestones help GME programs determine which of their trainees are on appropriate paths towards unsupervised clinical practice and which are not. Within a GME program, the clinical competency committee (CCC) forms a fundamental part of determining trainees' progress in the context of the Milestones, and some recent studies describe data sources that CCCs use and how they weigh this information in their collective decisions (Choe et al, 2016;Shumway et al, 2015). Several other studies have also looked at group decision making processes and how these concepts may be utilized by CCCs (Chahine et al, 2017;Hauer et al, 2016;Hemmer and Kelly, 2017).…”
Section: Introductionmentioning
confidence: 99%